Parametric design tools and how to take advantage of it in 3D sculptural design (Al-Academy, 2023)
The design was distinguished in Late Twenty-First Century With new and new methods Through which the ability to adapt all technical media in the formation of two-dimensional and three-dimensional figures and shapes was achieved .Which led to the emergence of endless sets of design ideas characterized by the heterogeneity of design forms and design solutions that preceded it. The designer could not access these creations in various architectural and artistic fields only through computer programs, especially those related to the activation of mathematical logic and what is known as algorithms in the formation and construction of the form, which led to the emergence of the "parametric direction" and the problem of research is summarized in the extent of the influence of parametric on the design The research aims to shed light on the emergence of parameter to shed light on the concept of parameter and its tools the research takes the approach (descriptive and analytical) spatial boundaries of some countries of the world, for example, but not limited to since the appearance of parameter until now, and the researcher offered a formative reading of some objects Museum parametric sculpture and a formative reading of some parametric sculptural objects in the open air One of the results of the research is that the sculptor, through the use of parametric, is able to design works for display internally in facilities or externally in squares and gardens, and that the parametric artist has knowledge of the elements that must be taken into account when designing models for museum display or garden display and outdoors, and the researcher recommends the need to pay attention to contemporary techniques in the field of Arts and direct scientific research in the field of Arts in general and sculpture in particular to discuss recent developments and discoveries in the fields of design and implementation of models in different countries of the world.